2018
DOI: 10.1016/j.compenvurbsys.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between the cost effectiveness of CCTV and improved street lighting as a means of crime reduction

Abstract: The effectiveness of CCTV and improved street lighting has been studied extensively in terms of their potential for reducing the number of crimes in a certain area. However, this does not take into account the cost of the interventions or the savings due to crime reduction. This paper presents a model, which takes the form of a cellular automaton to simulate the implementation of improved street lighting and CCTV cameras using a range of strategies. This permits an exploration of simulated options to find whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 4 publications
1
33
0
1
Order By: Relevance
“…At the very beginning of the project, two community workshops were conducted: an afternoon session with 25 participants and an evening session with 10 participants. The results of the community workshops and the feedback from city urban planners highlighted the need for a sensor monitoring the traffic with the following requirements:Multi-modal detection and tracking: The sensors need to be able to detect and track pedestrians, vehicles and cyclists.Privacy compliant: As sensors are going to be deployed over a city, the sensors should be privacy compliant, meaning that no personal data should be stored or exchanged.Leveraging existing infrastructures: As cities already make huge investments on CCTV systems [8], the solution should take advantage of the already existing infrastructures in terms of networks and cameras. Retrofitting the existing CCTV network to collect more data has been identified as a major innovation.Scalability and interoperability: New sensors can be added at any time, regardless their technologies, meaning the sensor of network can be easily expanded and capture new type of data.…”
Section: The Liverpool Smart Pedestrians Projectmentioning
confidence: 99%
See 2 more Smart Citations
“…At the very beginning of the project, two community workshops were conducted: an afternoon session with 25 participants and an evening session with 10 participants. The results of the community workshops and the feedback from city urban planners highlighted the need for a sensor monitoring the traffic with the following requirements:Multi-modal detection and tracking: The sensors need to be able to detect and track pedestrians, vehicles and cyclists.Privacy compliant: As sensors are going to be deployed over a city, the sensors should be privacy compliant, meaning that no personal data should be stored or exchanged.Leveraging existing infrastructures: As cities already make huge investments on CCTV systems [8], the solution should take advantage of the already existing infrastructures in terms of networks and cameras. Retrofitting the existing CCTV network to collect more data has been identified as a major innovation.Scalability and interoperability: New sensors can be added at any time, regardless their technologies, meaning the sensor of network can be easily expanded and capture new type of data.…”
Section: The Liverpool Smart Pedestrians Projectmentioning
confidence: 99%
“…Leveraging existing infrastructures: As cities already make huge investments on CCTV systems [8], the solution should take advantage of the already existing infrastructures in terms of networks and cameras. Retrofitting the existing CCTV network to collect more data has been identified as a major innovation.…”
Section: The Liverpool Smart Pedestrians Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the main findings of this study and against the prevalent notion that effective preventive 27], we postulate that a combination we postulate that a combination of the two prevention measures in the form of smart lights will yield the best results not only in terms of public security but also probably in terms of cost-efficiency.…”
Section: Discussionmentioning
confidence: 80%
“…The finding that the efficiency of CCTV depends heavily on the implementation strategy and location of the CCTV installation is in line with the findings of other studies which focused more on the costefficiency of CCTV and street lighting as crime deterrence instruments. Lawson and colleagues [27] for instance, assessed the cost-effectiveness of both, CCTV and street lighting, on crime and found that improved street lighting is in most cases more costeffective than CCTV, except within the context of crime hot spots, where CCTV is the better and more cost-effective method to reduce crime [27].…”
Section: Cctv and Crimementioning
confidence: 99%